Frequent generation of oncogenes by in vitro recombination of TRK protooncogene sequences. - Oskam, R (1988)
Transfection of NIH 3T3 cells with cDNA clones containing either the entire coding sequences or the tyrosine protein kinase domain of the human TRK protooncogene results in the frequent generation of transforming genes. Activation of most of these TRK oncogenes involves acquisition of DNA sequences. These sequences, unlike those present in the original human TRK oncogene, are not derived from tropomyosin genes. The products of these in vitro-generated TRK oncogenes retain the parental tyrosine protein kinase activity and contain an intact carboxyl terminus. However, they exhibit distinct biochemical properties. Whereas some of them are nonglycosylated cytoplasmic molecules, others were found to be transmembrane glycoproteins. These results suggest that TRK oncogenes may induce malignant transformation by allowing their tyrosine kinase to interact with various substrates depending on the nature of their activating sequences. If so, the TRK kinase may serve as a pleiotropic marker to identify various cellular proteins whose unscheduled phosphorylation on tyrosine residues contributes to neoplastic transformation.